Studi Empiris Faktor Penentu Kinerja UMKM Kuliner Kota Padang Provinsi Sumatera Barat - Rosa, Yenni Del; Idwar, Idwar; Imbikri, Muhammad; Ayu, Putri Murni (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The research objective is to determine the influence of digital technology, competitiveness, business strategy and innovation on the performance of Padang city culinary MSMEs. The research method uses an associative method with a quantitative approach. The research population was 4,454 culinary MSMEs and a sample of 135 MSMEs was taken by purposive sampling using the Rao soft sample size calculator technique. The data collection technique uses a questionnaire. All instrument tests and classical assumption tests are met before the data is processed. Multiple linear regression results Y = 1.375 + 0.879X1 + .784X2 + 0.693X3 + 0.791X4 + e. Hypothesis testing at a significance level of 5% shows that digital technology, competitiveness, business strategy and innovation have a significant positive effect on the performance of culinary MSMEs in the city of Padang, West Sumatra province, partially and simultaneously.